"Dejarse caer para después poder quizá levantarse ..." o el tema mitológico del descenso a los infiernos en Rayuela de Julio Cortázar - Šega, Agata (Ars et humanitas, 2015)
Twentieth-century literature frequently made use of classical mythology, and in Hispano-American literature especially Jorge Luis Borges and Octavio Paz come to mind in the regard, while Julio Cortázar also deserves mention. This paper aims to analyse from this perspective a few scenes from his novel Rayuela (Hopscotch). It will attempt to uncover the hidden meaning of seemingly quotidian events in the novel which, in addition to the direct and the superficial, contain an even deeper symbolic and archetypical meaning. Of primary interest are the motifs, actions, and characters in the novel which evoke the mythological theme of entering the underworld. This motif, which is closely linked with the motif of rising from the dead, is repeated in many classical myths and often appears in both older and contemporary literature. Relying on Carl Gustav Jung's theory, according to which mythological content represents innate and inherited forms of the human mind, the paper highlights those symbolic representations in Cortázar that are linked to mythological material and which are shown in a banal and trivial form in various chapters of the novel Hopscotch, especially in chapters 36 and 54. This is no coincidence, as it is precisely in these two places that the main protagonist, Cortázar's seeker, enters an initiation phase for development of his personality and with that commences the long journey to the other side which is in fact a Jungian journey to himself, to his own essence.
Keywords: argentinska književnost; Cortázar; Cortázar, Julio; Cortázar, Julio: Ristanc; literarne študije; mitologija; mythology; podzemlje